African cities and the development conundrum - Ammann, Carole; Förster, Till (International development policy, 2018)
This 10th thematic issue of International Development Policy presents a collection of articles exploring some of the complex development challenges associated with Africa's recent but extremely rapid pace of urbanisation that challenges still predominant but misleading images of Africa as a rural continent. Analysing urban settings through the diverse experiences and perspectives of inhabitants and stakeholders in cities across the continent, the authors consider the evolution of international development policy responses amidst the unique historical, social, economic and political contexts of Africa's urban development.